Decomposition and nutrient release pattern of animal manures biodegraded by fly larvae in Acrisols - Bloukounon-Goubalan, A. Y.; Saïdou, A.; Obognon, N.; AMADJI, Guillaume Lucien; Igué, A. M.; Clottey, V. A.; Kenis, M. (My University, 2018)
This study aims to assess the decomposition of manure biodegraded by fly larvae and the nutrient mineralization rates to understand the efficiency of the biodegraded manures for further use as soil amendment. A litter bag experiment was carried out over 75 d in an Acrisol in Benin using poultry manure, pig manure, mixture of poultry and sheep manure, mixture of poultry and cow manure, and mixture of poultry and pig manure, biodegraded by Musca domestica larvae. Nutrients content in the manures during the different stages of decomposition was analyzed. The mono-component exponential model Yt = Y0 × e−kt best described the manure decomposition and nutrients mineralization. The manures decomposed fast in the soil, and their nutrients were released fast in the poultry manure, the mixture of poultry and pig manure, and the mixture of poultry and cow manure. Nutrient mineralization increased in the order of P < N < K or N < P < K. Biodegradation of animal manures by fly larvae produced high-quality organic fertilizer through fast N and P release. This could aid in reducing the quantities of these elements applied as mineral fertilizer by farmers for sustaining agricultural soil productivity.
Keywords: organic manures; mineralization; fly larvae; soil fertility; modelling